Through Sadness to Sustainability: How Meaning Threat Sparks Sustainable Consumption - Kaminskiene, Zivile; Barsyte, Justina; Uzdavinyte, Elze (Organizations and Markets in Emerging Economies, 2025)
Prior research has highlighted that negative emotions have motivational features toward positive changes; however, findings are mixed and rather limited when it comes to the consumption domain. The present research expands existing perspectives on the motivational role of the negative emotion of sadness, which serves as a mechanism directed toward preventing losses in the future. With our research, we offer evidence that exposure to a meaning threat increases sadness. Moreover, the current research shows the direct effect of meaning threat on sustainable consumption. Most importantly, we demonstrate the mediating role of sadness and test this underlying process with different sustainable products. Theoretical and managerial implications are discussed, along with suggestions for future research.
Keywords: Meaning Threats; Sadness; Sustainable Consumption; Motivation